Mü’minun Suresi’nin din eğitimi açısından değerlendirilmesi - Günler, Serdar (My University, 2008)
Name of Thesis: The Analyse of Surah of “el-Muminun” in The Perspective of Education of Religion. Supervisor: Prof. Dr. H. Mahmut ÇAMDİBİ Writer: Serdar GÜNLER The human being isn’t a thing with one side and aspect but it has different sides. It is composed of body, soul and mental; It has various willings, desires and inclinations; on the other hand he has a great responsibility of its doings. So the holy “Quran” aims the human to be known and educated so that it develops itself, acquires its personality and wins the happiness in its life and afterlife. As a divine book, Quran offers an ideal type of “Mumin”. In the holy Quran Allah, who knows and explains the human being best, talks about it lengthy so guides and trains the human being and wants it to establish a system based on İslamic morals in the worldwide. In our thesis, because of its great importance, we studied on to analyse the general characteristic of “mumin” in the context of Surah “el-Muminun” and generally utilized from education books, tefsirs, dictinaries and encyclopedias. Our study has three parts. first part contains an introduction of the subject. In this introduction the improtance, aim and method of our study are explained. After that arabic form of the surah and a about it are presented. At the second part studied on the general characteristic of “Mumin” (the phenomenon of salvation) in the context of Surah “el-Muminun” in the perspective of education of religion. At the the third part, the principles of moral development (issues of taking lesson and tevekkul, lawful ‘helal’ morsel and vus’at ‘comfort’, acting in consciousness and unity and the phenomenons of teblig ‘rescript of Allah’, sabr ‘to be patient’ and dua ‘to pray’) are handled and discussed. Finally, with a result part, our study is ended.

Name of Thesis: The Analyse of Surah of “el-Muminun” in The Perspective of Education of Religion. Supervisor: Prof. Dr. H. Mahmut ÇAMDİBİ Writer: Serdar GÜNLER The human being isn’t a thing with one side and aspect but it has different sides. It is composed of body, soul and mental; It has various willings, desires and inclinations; on the other hand he has a great responsibility of its doings. So the holy “Quran” aims the human to be known and educated so that it develops itself, acquires its personality and wins the happiness in its life and afterlife. As a divine book, Quran offers an ideal type of “Mumin”. In the holy Quran Allah, who knows and explains the human being best, talks about it lengthy so guides and trains the human being and wants it to establish a system based on İslamic morals in the worldwide. In our thesis, because of its great importance, we studied on to analyse the general characteristic of “mumin” in the context of Surah “el-Muminun” and generally utilized from education books, tefsirs, dictinaries and encyclopedias. Our study has three parts. first part contains an introduction of the subject. In this introduction the improtance, aim and method of our study are explained. After that arabic form of the surah and a about it are presented. At the second part studied on the general characteristic of “Mumin” (the phenomenon of salvation) in the context of Surah “el-Muminun” in the perspective of education of religion. At the the third part, the principles of moral development (issues of taking lesson and tevekkul, lawful ‘helal’ morsel and vus’at ‘comfort’, acting in consciousness and unity and the phenomenons of teblig ‘rescript of Allah’, sabr ‘to be patient’ and dua ‘to pray’) are handled and discussed. Finally, with a result part, our study is ended.
Keywords: Din; Din Eğitimi; İslam Dini; Sureler